Multidimensional Isotropic Magnetic Shielding Contour Maps for the Visualization of Aromaticity in ortho-Arynes and Their Reactions - Artigas, Albert; Hagebaum-Reignier, Denis; Carissan, Yannick; Coquerel, Yoann (Synthesis, 2022)
Visualization of electron delocalization and aromaticity in some selected arynes, including nonplanar examples, and their Diels–Alder or dimerization reactions was achieved through multidimensional isotropic magnetic shielding contour maps. These maps showed that arynes are generally less aromatic than the corresponding arenes, and that aromaticity peaks during their reactions when approaching the transition state.
Keywords: arynes; aromaticity; DFT calculations; contorted molecules